KARAKTERISTIK PENGUNJUNG OBJEK WISATA PIUGUS RESORT DESA BELIBAK DI KEPULAUAN ANAMBAS RIAU - Paten Safira; Andri Wibowo; Arina Luthfini Lubis (Journal of Tourism and Interdiciplinary Studies, 2023)
Belibak is a village in Palmatak District, Anambas Islands Regency, Riau Islands Province. Belibak was designated as a "new tourism" village by Mr. Abdul Haris, the regent of Anambas Regency in 2015. Among those small islands, Anambas has five big separate lands that could be new tourism potential, namely Belibak, Piugus, Pidik, Mantang Besar and Mantang Kecil. Piugus Resort in Belibak village is known for its calm and quiet beach which attracts tourists to come to visit. In this research the author analyzes the characteristics of visitors to the Piugus Resort tourist attraction in Belibak village. The atmosphere of Piugus Resort, which is not as busy as other tourist attractions, encourage this research to be carried out. This research aims to determine the characteristics of visitors based on the characteristics of travel patterns. The method used in this research is a qualitative descriptive method and data was collected using a direct interview method with the management of Piugus Resort. The results of this research show that tourists visiting Piugus Resort have varying characteristics. In terms of destination, tourists who come to visit Piugus Resort have the aim of vacationing and resting. Visitors who come to Piugus Resort are mostly foreign tourists. The travel to get to Piugus Resort is five minutes by speedboat from Belibak village or 15 minutes by sea-motorbike. In term of length of stay at Piugus Resort is more than 24 hours to a month's stay. Most tourists who come to visit Piugus Resort to stay overnight, travel and spend holidays together, especially with colleagues or with family.